Systém odměňování zaměstnanců ve vybrané společnosti a návrhy na jeho zlepšení - Šťastná, Simona (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Bakalářská práce se zabývá systémem odměňování zaměstnanců ve vybrané společnosti a přináší návrhy na změny, které by měly zvýšit spokojenost zaměstnanců. Je strukturována do tří hlavních částí: teoretické, analytické a návrhové. Teoretická část využívá odbornou literaturu k detailnímu vysvětlení systému odměňování zaměstnanců. Analytická část se zaměřuje na analýzu stávajícího systému odměňování v dané společnosti. V návrhové části jsou pak navržena opatření, která by měla vést k lepšímu systému odměňování zaměstnanců a zvýšení jejich spokojenosti.

The bachelor thesis deals with the employee remuneration system in a chosen company and brings suggestions for changes that should increase employee satisfaction. It is structured into three main parts: theoretical, analytical and design. The theoretical part uses professional literature to explain the employee remuneration system in detail. The analytical part focuses on the analysis of the existing remuneration system in the company. In the design part, measures are presented that should lead to a better employee remuneration system and increase their satisfaction.
Employee remuneration system in the selected company and proposals for its improvement
Keywords: Odměňování; systém odměňování; zaměstnanec; zaměstnavatel; zaměstnanecké benefity; Remuneration; remuneration system; employee; employer; employee benefits